The impact of HMG on follicular fluid hormone levels, embryo quality and IVF outcome - (:unkn) unknown (Yuzuncu Yil Universitesi Tip Fakultesi, 2014)
The objective of this study is to evaluate the effect of HMG on the follicular fluid hormone levels, embryo quality and IVF outcomes when added at different times of stimulation to rFSH in a long protocol. Seventy infertile women were randomized into three groups; group 1(n=23) was stimulated only with rFSH; whereas, HMG was added from the beginning (group 2, n=23) or when a 10 mm follicle developed (group 3, n=24). Follicular fluid hormone levels, day 3 embryo quality, implantation and clinical pregnancy rates were assessed. The number of grade 1 embryos, and estradiol/ progesterone ratio were significantly higher in group 2 compared to group 1. The numbers of grade 2 and 3 embryos, and day 3 embryos with less than 5 cells were significantly higher in group 1. Clinical pregnancy rate was significantly higher in group 2 than group 1. In conclusion, HMG supplementation to rFSH does not increase the number of oocytes retrieved, the number of day 3 embryos and day 3 embryos at 8-cell or more stages of development, fertilization and implantation rates. HMG supplementation from the beginning of rFSH stimulation result in improvement of clinical pregnancy rates and other indices of embryo quality such as embryo grading.
Keywords: Embryo quality; Follicular fluid; FSH; Gonadotropins; IVF/ICSI outcome